2004
DOI: 10.1111/j.1939-1676.2004.tb02612.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Once‐Daily Amikacin in Healthy Foals and Therapeutic Drug Monitoring in Hospitalized Equine Neonates

Abstract: The objectives of this study were to investigate the pharmacokinetics of once-daily amikacin in healthy neonates, to determine amikacin concentrations in hospitalized foals, and to determine the minimum inhibitory concentrations (MICs) of amikacin against gram-negative isolates from blood cultures in septic foals. Median half-life, clearance, and volume of distribution of amikacin in healthy 2-to 3-day-old foals after administration of an intravenous bolus of amikacin (25 mg/kg) were 5.07 hours (4.86-5.45 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
7
22
0
Order By: Relevance
“…After comparison of pharmacokinetic parameters of amikacin found in our study with those found in foals after i.v. administration of amikacin once a day at high doses (21 and 25 mg/kg bwt) (Bucki et al 2004;Magdesian et al 2004); the mean peak plasma concentration extrapolated at time zero (C0) was similar with the one reported by Magdesian et al (2004). The zero-time plasma drug concentration intercept of the elimination phase was significantly higher than those reported for foals; indicating higher concentrations of amikacin after the distribution phase.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…After comparison of pharmacokinetic parameters of amikacin found in our study with those found in foals after i.v. administration of amikacin once a day at high doses (21 and 25 mg/kg bwt) (Bucki et al 2004;Magdesian et al 2004); the mean peak plasma concentration extrapolated at time zero (C0) was similar with the one reported by Magdesian et al (2004). The zero-time plasma drug concentration intercept of the elimination phase was significantly higher than those reported for foals; indicating higher concentrations of amikacin after the distribution phase.…”
Section: Discussionsupporting
confidence: 78%
“…The clearance and renal elimination of aminoglycosides (amikacin or gentamicin) in foals was shown to increase with age. Lower values for MRT, t1/2a, t1/2b and AUC were reported in older foals (Cummings et al 1985;Golenz et al 1994;Bucki et al 2004;Magdesian et al 2004). The volume of distribution of amikacin also decreased in foals as they aged (Bucki et al 2004).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this case, at the time the foal was treated, dosing three times per day was deemed most legally defensible, and with the supplementation of fluid therapy so as to protect the foal's kidneys, safe and efficacious. The current recommendation for dosing of amikacin is 25 mg/kg administered once daily [9]. No corticosteroids were given for treatment of possible NI because of lack of symptoms and the contraindication of suspected septicemia.…”
Section: Treatment and Outcomementioning
confidence: 99%